Ambulatory blood pressure adaptations to high-intensity interval training: a randomized controlled study. Issue 2 (February 2021) - Edwards, Jamie J.; Taylor, Katrina A.; Cottam, Christian; Jalaludeen, Navazh; Coleman, Damian A.; Wiles, Jonathan D.; Sharma, Rajan; O'Driscoll, Jamie M.
Abstract : Objective: Hypertension remains the leading cause of cardiovascular disease and premature mortality globally. Although high-intensity interval training (HIIT) is an effective nonpharmacological intervention for the reduction of clinic blood pressure (BP), very little research exists regarding its effects on ambulatory BP. The aim of this study was to measure alterations in ambulatory and clinic BP following HIIT in physically inactive adults. Methods: Forty-one participants (22.8 ± 2.7 years) were randomly assigned to a 4-week HIIT intervention or control group. The HIIT protocol was performed on a cycle ergometer set against a resistance of 7.5% bodyweight and consisted of 3 × 30-s maximal sprints separated with 2-min active recovery. Clinic and ambulatory BP was recorded pre and post the control period and HIIT intervention. Results: Following the HIIT intervention, 24-h ambulatory BP significantly decreased by 5.1 mmHg in sBP and 2.3 mmHg in dBP ( P  = 0.011 and 0.012, respectively), compared with the control group. In addition, clinic sBP significantly decreased by 6.6 mmHg compared with the control group ( P  = 0.021), with no significant changes in dBP and mean BP (mBP). Finally, 24-h ambulatory diastolic, daytime sBP, mBP and dBP, and night-time sBP and mBP variability significantly decreased post-HIIT compared with the control group. Conclusion: HIIT remains an effective intervention for the management of BP. Our findings support enduring BP reduction and improved BP variability, which are important independent risk factors for cardiovascular disease.